2010
DOI: 10.1007/s11250-010-9759-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of supplementation with urea, blood meal, and rumen-protected methionine on growth performance of Holstein heifers grazing kikuyu pasture

Abstract: Supplements with corn grain, molasses cane, and different nitrogen sources were evaluated in 16 growing Hosltein heifers [227 ± 33 kg body weight (BW)] grazing kikuyu (Pennisetum clandestinum) pasture in a 10-ha sward (rotational grazing with electric fences) during 90 days in the summer season. The nitrogen sources were urea (U); urea and blood meal (U+BM); and urea, blood meal, and rumen-protected methionine (U+BM +RPM). Heifers were randomly assigned to four experimental supplements defined as follows: cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 19 publications
0
8
0
1
Order By: Relevance
“…Sanchez et al (2012) evaluated 5 g/d of RPM in growing lambs fed with rations based on corn stover and did not find any effects of the amino acid on growth, intake or feed efficiency. In contrast, Gomez et al (2011) demonstrated that grazing heifers exhibited improved growth in response to the dietary addition of RPM when a source of bypass Lys was included in the supplement. Madsen et al (2005) found a positive effect in dairy goats in milk production, but only when Met was combined with rumen-protected Lys at a Lys to Met ratio of 2.55 : 1.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Sanchez et al (2012) evaluated 5 g/d of RPM in growing lambs fed with rations based on corn stover and did not find any effects of the amino acid on growth, intake or feed efficiency. In contrast, Gomez et al (2011) demonstrated that grazing heifers exhibited improved growth in response to the dietary addition of RPM when a source of bypass Lys was included in the supplement. Madsen et al (2005) found a positive effect in dairy goats in milk production, but only when Met was combined with rumen-protected Lys at a Lys to Met ratio of 2.55 : 1.…”
Section: Resultsmentioning
confidence: 90%
“…Previous experiments using rumen-protected methionine (RPM) in growing lambs have not been successful, presumably because the diets were based on low-quality forage with inadequate lysine (Lys) and Met flows (Sanchez et al, 2012). In contrast, grazing heifers supplemented with RPM and complemented with sources of bypass Lys improved average daily gain (ADG) (Gomez et al, 2011). The NRC (2007) indicated that choline requirements have not been established for sheep, but suggested that production could be improved by using it as a supplement.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been found that the total and average daily weight gain of heifers supplemented with U (urea) + BM (blood meal) + RPM (rumen‐protected methionine) were higher than the corresponding rates of heifers either not supplemented or supplemented with U or U + BM (Gomez et al . ).…”
Section: Introductionmentioning
confidence: 97%
“…Some grazing experiments with cattle have shown positive responses of the growth of steer to the dietary addition of RPM (Gomez et al 2011), whereas other studies have shown no effect (Liker et al 2006) at doses of 10 g/day. The reason that the intermediate dose decreased weight gain in this experiment is unclear, but the possibility that deer respond to higher doses than those used in this experiment should not be excluded.…”
Section: Discussionmentioning
confidence: 97%